Meneropong Fenomena Flexing dalam al-Qur’an: Analisis Semantik QS. Al-Ḥadīd [57]: 20 - Nur Shadiq Sandimula; Syarifuddin Syarifuddin; Ridwan Jamal (Universitas Darussalam Gontor, 2024)
Advancements in information technology and its central feature of global connectivity permit the exchange of information and interactions among diverse cultures and religions. Social media platforms have released the boundaries of geographical stretch and demographic regions that approve the infiltration of particular mindsets, lifestyles, and behavioral tendencies. The use of social media in the public sphere has led to a distinctive social behavior in the form of lifestyle dubbed flexing. The flexing lifestyle is a behavioral phenomenon to exhibit one's wealth and self-achievement to urge society to be wasteful. This study aims to examine the phenomenon of flexing from the perspective of the Qur'an; analyze the term al-ḥayāt al-dunyā in the verse of QS. al-Ḥadīd [57]: 20. This research employs interpretive-qualitative analysis using a semantic analysis approach designed by Syed Muhammad Naquib al-Attas in examining conceptual meanings in the Qur'an. The results of this study indicate that flexing is a nefarious consumption behavior in socio-economic theory refers as emulative consumption. This behavior has become a lifestyle and has impacted the community's mode of living. This lifestyle in the Qur'anic term is called al-ḥayāt al-dunyā, semantically a lowly lifestyle. This concept emerges from a semantic analysis of the phrase al-ḥayāt al-dunyā comprising the meanings la'ib (game), lahw (joking), zīnah (things that are dear to human lust), tafākhur (proud of one's achievements in facade of people), takāṡur (competing in the accumulation of wealth), farḥ (momentary happiness), matā' (temporary pleasure), and ghurūr (something that deceives). In the light of the Qur'an, this behavior is a demeanor mode of living, because it disregards the disobedient from remembering God and the afterlife.